THE INFLUENCE OF THE PRINCIPAL'S TRANSFORMATIONAL LEADERSHIP AND SCHOOL CULTURE ON TEACHER PERFORMANCE AT SDN PURUT - Sari, Neneng Tri Wulan; Sariwardani, Andriani; Dewi, Ratna; Umalihayati, Umalihayati (Cakrawala Pedagogik, 2025)
This study aims to find out the influence of transformational leadership of school principals and school culture on teacher performance at SDN Purut. The research uses a quantitative a correlational approach involving all teachers at SDN Purut as respondents, consist of 11 teachers. The research instruments are questionnaires developed based on indicators of transformational leadership, school culture, and teacher performance variables. Descriptive analysis results shows that transformational leadership of the school principal is categorized as high and very high, school culture is classified as very high, and teacher performance is generally categorized as high and very high. Inferential analysis shows that partially, transformational leadership significantly influences on teacher performance with a correlation coefficient (R) = 0.643 and coefficient of determination (R²) = 0.413. School culture also significantly influences with R = 0.634 and R² = 0.402. Simultaneously, both variables give a very significant effect on teacher performance with R = 0.993 and R² = 0.987. It shows that 98.7% of the variation on teacher performance can be explained by transformational leadership and school culture. It can be concluded that transformational leadership and a strong school culture play an essential role in improving teacher performance. Therefore, strengthening an inspirational leadership style and creating a positive school culture should be continuously developed to improve the quality of education.